EFEKTIVITAS PENGGUNAAN LIMBAH AIR CUCIAN BERAS DALAM MENGURANGI PENGGUNAAN PUPUK NPK MUTIARA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays L.) - Anwar, Anwar; Yusuf, Mani; Rizal, Abdul; Endrawati, Tri (Universitas Islam Balitar, 2023)
Zea mays L. is one of the food crops that people like because it has a lot of nutritional content. In increasing the growth and production of Zea mays L. plants, it can be done by integrating rice washing water waste with inorganic fertilizers in order to minimize the use of chemical fertilizers. The purpose of this study was to determine the effect of using rice washing water waste in reducing the use of pearl NPK on vegetative growth and production of Zea mays L. plants. This research was carried out at the Greenhouse of the Agrotechnology Study Program, Faculty of Agriculture, Musamus University in June - September 2022 with a cultivation scale in polybaq. The design used was a completely randomized design (CRD) with 7 treatments and 3 replications, namely: K0 = Control; K1=rice washing water without pearl NPK; K2=rice washing water+25% pearl NPK; K3=rice washing water+50% pearl NPK; K4=rice washing water+75% pearl NPK; K5 = rice washing water + 100% pearl NPK; A6= 100% NPK pearl. Parameters observed were: plant height, number of leaves, stem diameter, leaf area, cob weight, cob weight without cob, number of rows of seeds per ear, cob diameter, cob length, and 100 seed weight. Observations were analyzed using the method of variance. If there are significantly different treatments, then proceed with the BNT test at the 95% confidence level. The results showed that the treatment of rice washing water + pearl NPK had a significant effect on the growth and production of Zea mays L.. Based on data from the analysis carried out by treating rice washing water waste + 50 % to 75% Pearl NPK can increase the vegetative and generative growth of corn plants so as to minimize the use of inorganic fertilizers by 25% -50% of the recommended dose. Keywords: Rice washing water, Zea mays L., Pearl NPK Fertilizer